2018
DOI: 10.14814/phy2.13944
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure reactivity at onset of mental stress determines sympathetic vascular response in young adults

Abstract: We have previously shown in young males that the rate of rise in blood pressure (BP) at the onset of mental stress determines whether or not muscle sympathetic nerve activity (MSNA) has a role in driving the pressor response. The aim of this study was to investigate these interactions in young females. BP and MSNA were recorded continuously in 19 females and 21 males during 2‐min mental stressors (mental arithmetic and Stroop test). Physical stressor tasks (cold pressor, handgrip exercise, postexercise ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…social stress), reduces the need for peripheral sympathetic activation to meet blood pressure requirements. Conversely, if the physiological system is not properly primed during the preparation phase, augmented peripheral sympathetic activity may be necessary to achieve the appropriate blood pressure response to the speech and maths portions, similar to the findings of El Sayed et al (2016Sayed et al ( , 2018. Whether reductions in MSNA in response to mental stress are beneficial remains to be determined, as this may simply indicate excessive reactivity at a different organ bed, such as the heart (Esler, 2022), which may be equally detrimental as excessive peripheral sympathetic activation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…social stress), reduces the need for peripheral sympathetic activation to meet blood pressure requirements. Conversely, if the physiological system is not properly primed during the preparation phase, augmented peripheral sympathetic activity may be necessary to achieve the appropriate blood pressure response to the speech and maths portions, similar to the findings of El Sayed et al (2016Sayed et al ( , 2018. Whether reductions in MSNA in response to mental stress are beneficial remains to be determined, as this may simply indicate excessive reactivity at a different organ bed, such as the heart (Esler, 2022), which may be equally detrimental as excessive peripheral sympathetic activation.…”
Section: Discussionmentioning
confidence: 73%
“…Despite wide inter ‐individual variability, intra ‐individual responses to mental stress and arousal appear to be reproducible (Donadio et al., 2002; Fonkoue & Carter, 2015). While the influence of factors such as baroreflex function (Anderson et al., 1991; Durocher et al., 2009, 2011), rate of blood pressure changes (El Sayed et al., 2016, 2018), psychological factors (Bigalke & Carter, 2021) and perceived stress (Callister et al., 1992; Carter et al., 2008) have been explored, a consensus has not yet been reached regarding the physiological underpinning of variations in stress reactivity. Many commonly utilized stress tests are performed with the addition of multiple confounds such as irregular breathing patterns and depth, active talking, muscle movements and other confounds that may impact MSNA recordings and subsequent data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A major determinant of blood pressure variability depends on baroreceptor sensitivity [ 21 ]. When the vascular structure changes significantly, it may reduce the sensitivity of arterial baroreceptors by limiting the extension of baroreceptors, and the lower sensitivity would be expected to lead to increased blood pressure variability [ 22 , 23 ]. Moreover, atherosclerosis itself may enhance blood pressure fluctuations associated with small changes in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Callister et al (4) reported that total MSNA from the radial nerve of the arm decreased when arterial pressure increased before starting voluntary leg-cycling exercise, although they did not examine whether cerebral activation and/or muscle vasodilation occurred before starting voluntary exercise. In addition, El Sayed et al (7) reported that during mental stress ⌬MAP peak was greater in subjects who experienced decreases in MSNA burst frequency of the peroneal nerve and suggested that the reduction in MSNA was likely caused by the baroreflex mechanism. These results suggest that the baroreflex accounts for the reduced MSNA in response to the increase in MAP during mental stress or preparation for starting voluntary exercise.…”
Section: Map Response To the CDmentioning
confidence: 99%